RELEVANSI HAQQUL 'ABDI MUQADDAMUN 'ALA HAQQILLAH DENGAN PRINSIP MAQASHID SYARIAH - Rahmadani, Rini; Fatmawati; Taufiq Sanusi, Nur (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
This research examines the concept of Haqqul 'Abdi Muqaddamun 'Ala Haqqillah (human rights take precedence over Allah's rights), which is a fiqh principle that emphasizes the importance of prioritizing the fulfillment of human rights in certain situations to prevent social damage or greater injustice. By using a normative and comparative analysis approach to Islamic sharia texts, this study connects this concept with the principles of Maqashid Syariah, which aims to realize benefit through the protection of religion, soul, mind, property and descendants. The results of the analysis show that the Haqqul 'Abdi concept is not only relevant in protecting individual rights, but also supports the application of the principles of restorative justice in modern Islamic law. In the context of Maqashid Syariah, this concept is the foundation for creating social harmony, upholding justice, and ensuring the sustainable welfare of the people.